2017
DOI: 10.3390/nu9070686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aged Garlic Extract on Cholinergic, Glutamatergic and GABAergic Systems with Regard to Cognitive Impairment in Aβ-Induced Rats

Abstract: Alzheimer’s disease (AD) has been linked to the degeneration of central cholinergic and glutamatergic transmission, which correlates with progressive memory loss and the accumulation of amyloid-β (Aβ). It has been claimed that aged garlic extract (AGE) has a beneficial effect in preventing neurodegeneration in AD. Therefore, the objective of this study was to investigate the effects of AGE on Aβ-induced cognitive dysfunction with a biochemical basis in the cholinergic, glutamatergic, and GABAergic systems in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 60 publications
2
32
0
Order By: Relevance
“…AGE possesses greater antioxidant activity than fresh garlic by scavenging reactive oxygen species (ROS), enhancing the activity of cellular antioxidant enzymes (e.g., superoxide dismutase, catalase and glutathione peroxidase), mainly observed following the administration of SAC in vivo (16), and increasing glutathione levels in cells (17)(18)(19). Several studies on both animals and humans have shown that AGE contributes to a reduced risk of cancer (20,21), cardiovascular disease (22)(23)(24), Alzheimer's disease and other age-related degenerative conditions (19,25). Moreover, the mode of action of AGE in inhibiting the formation of atherosclerosis in apolipoprotein E-knockout mice has been investigated by examining whether AGE suppresses inflammation (26).…”
Section: The Antioxidant Aged Garlic Extract Exerts Cytotoxic Effecmentioning
confidence: 99%
“…AGE possesses greater antioxidant activity than fresh garlic by scavenging reactive oxygen species (ROS), enhancing the activity of cellular antioxidant enzymes (e.g., superoxide dismutase, catalase and glutathione peroxidase), mainly observed following the administration of SAC in vivo (16), and increasing glutathione levels in cells (17)(18)(19). Several studies on both animals and humans have shown that AGE contributes to a reduced risk of cancer (20,21), cardiovascular disease (22)(23)(24), Alzheimer's disease and other age-related degenerative conditions (19,25). Moreover, the mode of action of AGE in inhibiting the formation of atherosclerosis in apolipoprotein E-knockout mice has been investigated by examining whether AGE suppresses inflammation (26).…”
Section: The Antioxidant Aged Garlic Extract Exerts Cytotoxic Effecmentioning
confidence: 99%
“…Ab peptide has injurious effects, such as cholinergic dysfunction and impaired memory abilities, in mice. 27 Also, the downregulation of BDNF levels and unusual CREB signals were exhibited by AD patients and AD mouse model. 9,10 Previous studies have reported that various phytochemicals and plant extracts could prevent neuronal cell death and promote the recovery of cognitive function and neurotrophic factor after Ab peptide challenge.…”
Section: Discussionmentioning
confidence: 98%
“…Several reports have identified the role of ROS production in Ab-induced neurotoxicity, and discussed how various phytochemicals or plant extracts suppressed Abinduced neurotoxicity. 27 To further investigate the effects of DLE on the enhancement of cognitive functions, an ICV injection of Ab 1-42 into the mouse brain served as an in vivo model of AD. An ICV injection of Ab 1-42 led to cognitive dysfunction.…”
mentioning
confidence: 99%
“…The neurotoxicity of Aβ has been reported to involve a number of neuronal events, such as the deficiency of neurotransmitters, and a decrease in vesicular transporters and synaptic transmissions, leading to neuronal cell death (41)(42)(43)(44). In addition, the effects of AGE on cholinergic, glutamatergic and GABAergic systems have been shown in rats with Aβ-induced cognitive impairment (45). AGE can significantly improve the working memory, as well as the reference memory of rats with Aβ-induced cognitive impairment in association with the amelioration of the loss of cholinergic neurons.…”
Section: Overview Of the Mechanisms Of Action Of Aged Garlicmentioning
confidence: 99%